7 SPHERES OF ACTION IN NETFLIX SERIES SHADOW AND BONE S1 (2021): A VLADIMIR PROPP’S THEORY PERSPECTIVE - Rahmah, Fathiyyah; Rahmi, Gita (Asosiasi Dosen Muda Indonesia, 2023)
ABSTRACT Seven spheres of action is a theory made by Vladimir Propp. The researcher analyzed the role of characters that appear in the Netflix series Shadow and Bone with this theory. The research method used is descriptive qualitative method. The result of this research shows there are six out of seven spheres of action that appear in this story which are: Alina Starkov as hero, King Pyotr as dispatcher, Baghra as donor, General Kirigan and Genya Safin as false hero, Malyen Oretsev, Zoya Nazyalensky, and The Crows (Kaz Brekker, Inej Ghava, Jesper Fahey) as helper, General Kirigan, Arken Visser, Dreesen, and General Zlatan as villain. The spheres of action the princess and her father did not appear in this series.